(untitled) (Journal of Partial Differential Equations, 1999)
In this paper a nonliuear system of second order equations of mixed type is considered. The existence of H¹ strong solution for the modified Tricomi problem is proved by the energy integral method and the Leray-Schauder's fixed point principle.